2010
DOI: 10.1002/nml.20014
|View full text |Cite
|
Sign up to set email alerts
|

Crisis in leadership or failure to plan?

Abstract: During the past ten years, succession planning and managing executive transitions have emerged as important issues inNote: We are indebted to the Annie E. Casey Foundation, which gave us permission to use the survey questions developed in Nonprofit Executive Leadership and Transition Survey (Teegarden, 2004). For more information on this survey and the foundation's research, see http://www.aecf.org/KnowledgeCenter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 9 publications
0
24
0
2
Order By: Relevance
“…Succession planning is a broad topic that includes identifying and assessing talent, developing leadership competencies, and building a pool of leadership candidates within an organization to ensure continuity in critical positions (Carman, Leland, & Wilson, 2010). Over the past five decades, CEO successions have been the topic of several research studies that examined the causes and implications of CEO successions.…”
Section: Background Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Succession planning is a broad topic that includes identifying and assessing talent, developing leadership competencies, and building a pool of leadership candidates within an organization to ensure continuity in critical positions (Carman, Leland, & Wilson, 2010). Over the past five decades, CEO successions have been the topic of several research studies that examined the causes and implications of CEO successions.…”
Section: Background Of the Problemmentioning
confidence: 99%
“…Succession planning is a broad topic that includes identifying and assessing talent, developing leadership competencies, and building a pool of leadership candidates within an organization to ensure continuity in critical positions (Carman, Leland, & Wilson, 2010). Succession planning is an approach to building a pipeline of leaders from whom the organization can draw for important future roles and to ensure continued effective performance for the organization in both emergency situations and predictable leadership transitions (Cavanaugh, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Based on the county migrations statistics 2010-2014 County is gaining population from migration. The number of inbound migration flows is 71,000 (39,495+24,338+7,167), while the number of outbound migration flows is 53,764 (28,133+25,631).…”
Section: Overall Trendsmentioning
confidence: 99%
“…In examining the trajectory of nonprofit executive leadership, research has shown that it is inconsistent across leaders, given that some are promoted based solely on tenure (Austin et al, 2011), while others are hired for their business acumen rather than their nonprofit knowledge (Suarez, 2010). Researchers have also found that, while current CEOs have become more aware of this looming leadership learning crisis, little has been done to actually address this need and to better understand how current CEOs learned to lead (Carman, Leland, & Wilson, 2010;Froelich et al, 2011;Kearns et al, 2015).…”
Section: Significance Of the Research Questionmentioning
confidence: 99%
“…Their findings revealed that a key indicator of transitional success is internal leadership; therefore, an organization must be responsible for the development of its leaders (Gothard & Austin, 2013). Relatedly, Carman et al (2010) recommended that organizations should focus on building leaders from within, not only on filling upcoming voids in executive leadership, but across all levels of agency leadership.…”
Section: Learning Nonprofit Leadershipmentioning
confidence: 99%